Development Of A Regression Model For Relationship Between Psychophysical And Biomechanics Factors Of Push Activities - Ani, Mohammad Firdaus; Kamat, Seri Rahayu; Mohd Ghazali, Athirah (The Human Factors And Ergonomics Society Malaysia (HFEM), 2017)
In aerospace industries, many working tasks require their workers to perform the works in push-pull activities. The workers need to push or pull the mould tool in a long distance in to a workplace. Performing these activities continuously throughout the working hours, may lead to an early initiation of musculoskeletal disorders (MSDs) symptoms as workers developed muscle fatigue particularly concerning the hand muscles. Grip strength is the force applied by the hand to pull objects and is a part of hand strength. Repetitive usage of hands will create an imbalance between closing and opening (antagonist) muscles, which can lead to problem such as carpal tunnel syndrome (CTS). The primary purpose of this study was to develop a regression model based on psychophysical and biomechanical factors that contributes to fatigue, in which the models can predict the relationship between the input parameters and output responses. The methodology used for this study focused on three types of data collection which were questionnaire and observation which conducted as the preliminary study to prove the problems that have been stated and experimental was conducted by using surface Electromyography (sEMG) and Tekscan system to evaluate the muscle fatigue and hand grip pressure force of the Lay-up workers who were performing push activity. This study investigates the hand grip pressure force for the right hand and left hand within 5 minutes and 10 minutes of time exposure while workers pushing the mould tool, and study the relationship between time exposure with hand grip pressure force and muscle fatigue. The input parameters evaluated were time exposure, hand side and body mass index (BMI); while the output responses are muscle fatigue (voltage), hand grip pressure force (left hand), and hand grip pressure force (right hand). Two polynomial equations were successfully developed and validated. The modelling validation runs were within 90% prediction interval of the developed models and their residual errors compared to the predicted values were less than 10%. The significant parameters that influenced the output responses were also identified. Muscle fatigue was influenced by time exposure, hand side, BMI, and interaction between hand side and BMI; while hand grip pressure force was influenced by time exposure, hand side, BMI, interaction between time exposure and hand side, interaction between time exposure and BMI, and interaction between hand side and BMI.